Concussion increases suicide risk - Assonov, Dmytro (Psychosomatic Medicine and General Practice, 2019)
In a quarter of patients after a traumatic brain injury chronic symptoms of anxiety and depression are observed. A new study answers the question whether a mild traumatic brain injury (concussion) is associated with an increased risk of suicidal thoughts, intentions and actions.